The Influence Of The Application Of The Interactive Powerpoint On The Cognitive Development Of AUD - Gusmaniarti Gusmaniarti; Nurul Afifah (Universitas Muhammadiyah Ponorogo, 2023)
Learning in early childhood can be done by utilizing various learning media, one of which is technology. Technology in early childhood learning can improve six aspects of child development, one of which is cognitive abilities. The interactive PowerPoint learning technology applied in this study provides a stimulus for cognitive development so children can acquire and build knowledge by discovering their knowledge. This study aimed to determine the effect of learning with interactive PowerPoint media on the cognitive development of early childhood in TK Aisyiyah 52. The research method used in this study was quantitative research with the study population of children aged 5-6 years. The type of sample used was Non-Probability sample selection using a saturated sampling technique with the same population as the research sample of 20 children. Data were obtained through the results of the pre-test and post-test scores. From the results of data analysis, it was found that the average score for the pre-test was 6, and the average score for the post-test was 12.25. This indicated that the average post-test score was higher than the average pre-test score for the t-count and t-table values, with a significant level of 5% and N = 20. Then, Ha was accepted, and Ho was rejected meaning that method using interactive PowerPoint media had an influence on the cognitive development of early childhood.